PENGUKURAN TINGKAT KEBISINGAN DI JALAN RAYA PEKANBARU-BANGKINANG SEBELUM DI BANGUN BEBAS HAMBATAN (HIGHWAY) - Mutiara Akhdesia; Erwin '; Defrianto ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Measurement of the noise level in the roadway of Pekanbaru-Bangkinang before building of Highway has been done. The sources of noise originated from the sound of vehicles that passed through the roadway. The level of noise has been measured by using a Sound Level Meter (SLM). The measurement of noise level carried out in two locations, first location was on roadway of Pekanbaru-Bangkinang KM 21 and the second location was at round aboard of Jalan Garuda Sakti and Jalan PekanbaruBangkinang. The noise level at first location was measured as a function of time from 07.00 until 18.00 pm during one week. In this research, the number of vehicles that passed through the first location have been counted every hour. Furthermore, the noise level was measured as a function of distance from the noise source using two SLMs, namely SLM type MS 6701 and SL 4112. The results showed that the noise level at the first location occurred on Saturday and Sunday at 16.00 to 18.00 with the highest value of 79.09 dBA and 78.28 dBA respectively, while the lowest noise value occurred on Friday at 12.00 to 13.00 pm with the value of 67.97 dBA. The highest noise level at the second location occurred at 17.00 to 18.00 with a value of 81.60 dBA. The value of noise level at the second location was higher compared to that of the first location. This was due to more number of vehicles that passed through that location compared to that of the first location. The profile of noise level occurred on Saturday was compared to that of the theoretical calculations. The result showed that both results had a similar characteristics. Moreover, the results of this research showed that the level of noise as a function of distance from the noise source was decrease with increasing the distance. The decrease of the noise level was caused by the absorption of the noise by the surrounding parameters such as air,vegetation and buildings nearby.